Student Problem-Solving Ability in Views of Self-Directed Learning on Problem Based Learning Assisted by Module (Unnes Journal of Mathematics Education Research, 2022)
This research described the required module patterns for the students based on the self-directed learning types to improve their problem-solving skills taught by problem-based learning. The applied design was qualitative descriptive. Thus, the research described the observed events qualitatively and quantitatively. The subjects consisted of 35 students of XI Science 4 at Senior High School Grabag, the academic year 2021/2022. The researchers took the data source with a purposive sampling technique by considering certain objectives. Then, the researchers collected the data with a self-directed learning questionnaire, problem-solving skill test, observation, and interview. The researchers analyzed the data qualitatively. The researchers also used N-gain analysis to determine the improvement. The results showed that (1) students with high self-directed learning applied the first module pattern in the form of a scaffolding technique to model the behaviors and provide an explanation, (2) students with moderate self-directed learning applied the second module pattern in the form of scaffolding technique to invite the participation of other students and to share the keywords; (3) studentss with low self-directed learning applied the third module pattern in the form of scaffolding to model the behavior, present explanation, participate, and invite other students by providing keywords; (4) improved problem-solving skills; and (5) reaching the minimum standard mastery for learning taught by problem-based learning assisted by module.